Analisis Kemampuan Pemecahan Masalah Matematika pada Siswa SMP dalam Menyelesaikan Soal Cerita Ditinjau dari Tahapan Polya - Krismonica Mawardi; Arjudin Arjudin; Muhammad Turmuzi; Syahrul Azmi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe the level of students’ problem solving ability in solving comparative material. This research is qualitative research designed to determine the level of mathematical problem solving ability of students in the subject of comparison. The population in this study were all eighth grade students of SMP Negeri 16 Mataram with a total of 127 students. The sampling technique used is a non- probability sampling technique with purposive sampling type. Collecting data in the form of tests and interviews. The instrument used is in the form of a problem-solving ability test which consists of 2 questions. The data analysis technique uses qualitative data analysis and quantitative data analysis. The results of this study indicate that the level of problem solving ability of students is mostly in the medium category with an average of 68.37. The level of mathematical problem solving ability was grouped into three categories, from 25 students it was found that 7 students had high problem solving abilities or with a percentage (28 %), students with moderate problem solving abilities were 9 students (%), and students with low problem solving abilities as many as 9 students (36 %).